High-strength corrugated carton based on waterproof agent and preparation method of high-strength corrugated carton
By using materials such as lignin derivatives, hydroxy-terminated polydimethylsiloxane and eugenol-modified thiol curing agents on corrugated cartons, polydopamine is synthesized in combination with enzymatic reactions, the problem of corrugated cartons being damp in a humid environment is solved, and its waterproof and wear resistance are significantly improved.
Patent Information
- Application Number
- CN202411901094.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Traditional corrugated cartons are prone to moisture in a humid environment, resulting in a decrease in the strength of the box and even deformation and damage, affecting the safety and integrity of the product. The existing waterproof treatment methods lack adhesion performance, resulting in the coating falling off and losing the waterproof effect.
Lignon derivatives and hydroxyl-terminated polydimethylsiloxane are used as the main waterproofing units and wear-resistant units, combined with eugenol-modified thiol curing agent, polydopamine is synthesized through enzymatic reactions to form a thiol curing agent with a dopamine structure, which closely connects the waterproofing agent with a waterproof enhancement additive to improve the adhesion and wear resistance of the coating.
It significantly improves the waterproof and wear resistance of corrugated cartons, enhances the bonding force between the coating and the carton surface, prevents the coating from falling off and local wear, and extends the service life of the packaging material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of corrugated paper boxes, in particular to a high-strength corrugated paper box based on a waterproofing agent and a preparation method thereof. Background Art
[0002] In the modern logistics and transportation industry, corrugated boxes are widely used as a major packaging material for packaging various commodities due to their advantages such as light weight, high strength, low cost and strong recyclability. However, in some special environments, such as transportation and storage conditions with high humidity or rain, traditional corrugated boxes are easily affected by moisture, resulting in a decrease in box strength, and even deformation and damage, affecting the safety and integrity of the commodities. Therefore, how to improve the water resistance and strength of corrugated boxes in a humid environment has become an important topic in the field of packaging material research and development.
[0003] In the prior art, the waterproof treatment of corrugated paper boxes mainly adopts the method of applying waterproof agent, which forms a waterproof coating on the surface of the paper box to improve its water resistance. However, the adhesion performance of these coating layers is often insufficient. Specifically, the adhesion between the coating and the paper box substrate is weak, and it is easy to fall off or peel off during transportation, folding or long-term storage. Insufficient adhesion makes it impossible for the coating to be effectively maintained on the surface of the paper box, thereby losing the waterproof effect and even affecting the overall strength and performance of the paper box.
[0004] Therefore, a high-strength corrugated paper box based on a waterproofing agent and a preparation method thereof are invented. Summary of the invention
[0005] The object of the present invention is to provide a high-strength corrugated paper box based on a waterproofing agent and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-strength corrugated paper box based on a waterproofing agent comprises the following preparation steps: S1: Add lignin to acetone, stir evenly, add palm oil concentrated sulfuric acid mixture, heat to 70-75°C under nitrogen atmosphere for reaction for 2.5-3h, cool to room temperature, wash the product with pentane, vacuum dry for 48h, grind and crush, sieve to obtain lignin derivative; S2: adding the lignin derivative to acetone, stirring evenly, adding silane coupling agent KH550, stirring and reacting at room temperature for 48 hours, adding dicyclohexylmethane diisocyanate, stirring and reacting at room temperature for 24 hours, washing the product with pentane, vacuum drying for 48 hours, grinding and crushing, sieving, and grafting the lignin derivative; S3: adding the grafted lignin derivative and hydroxyl-terminated polydimethylsiloxane to a reaction container, adding dibutyl tin dilaurate, heating to 70-75°C under a nitrogen atmosphere for reaction for 4-4.5 hours, adding 1,4-butanediol and N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide, keeping the temperature for reaction for 4-4.5 hours, adding methanol, keeping the temperature for stirring for 2-3 hours, and vacuum drying for 48 hours to obtain a waterproofing agent; S4: Add a thiol curing agent containing a dopamine structure into tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent into tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply a waterproofing enhancer on the surface of the corrugated box, and then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1-2 hours, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
[0007] Furthermore, the coating thickness of the waterproof enhancer is 20-30 μm, the coating thickness of the curing agent solution is 10-20 μm, and the coating thickness of the waterproofing agent solution is 20-30 μm.
[0008] Furthermore, in the preparation process of the lignin derivative, every 1g of lignin is dissolved in 10mL of acetone, and the mass ratio of the acetone solution of lignin to the palm oil concentrated sulfuric acid mixture is 1:(1-2), and in the palm oil concentrated sulfuric acid mixture, 0.1mL of concentrated sulfuric acid is added to every 15g of palm oil.
[0009] Furthermore, in the preparation process of the grafted lignin derivative, the molar ratio of silane coupling agent KH550:lignin derivative:dicyclohexylmethane diisocyanate is 1:(5-6):(2-4).
[0010] Furthermore, in the preparation process of the waterproofing agent, the molar ratio of the grafted lignin derivative: hydroxyl-terminated polydimethylsiloxane: 1,4-butanediol: bis(4-hydroxyphenyl) disulfide is (15.5-20.5):(3-10):7:3.
[0011] Furthermore, the preparation method of the thiol curing agent containing a dopamine structure comprises the following steps: step (1): adding eugenol and triethylsilane into a reaction container, stirring evenly, adding tri(pentafluorophenyl)borane twice, reacting at room temperature for 12 hours, adding dichloromethane to dilute, removing impurities with alkaline alumina, and distilling under reduced pressure to obtain grafted eugenol; Step (2): adding grafted eugenol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 2,2-dimethoxy-2-phenylacetophenone into tetrahydrofuran, purging the solution with nitrogen for 5-10 minutes, irradiating with ultraviolet light for reaction for 1-1.5 hours, filtering impurities with a 0.2 μm syringe filter, and distilling under reduced pressure to obtain grafted pentaerythritol tris(3-mercaptopropionic acid) ester; Step (3): Add the grafted tri(3-mercaptopropionic acid) pentaerythritol ester into tetrahydrofuran, add hydrochloric acid, stir and react for 24 hours, and distill under reduced pressure to obtain a thiol curing agent containing a dopamine structure.
[0012] Furthermore, in the preparation process of the grafted eugenol, the mass ratio of eugenol to triethylsilane is (5.15-5.2):(14.8-15). The interval between the two additions of tris(pentafluorophenyl)borane is 1 hour.
[0013] Furthermore, in the preparation process of the grafted tris(3-mercaptopropionic acid) pentaerythritol ester, the mass ratio of grafted eugenol:tetrakis(3-mercaptopropionic acid) pentaerythritol ester is (3.5-3.6):(4.7-4.8).
[0014] Furthermore, during the preparation of the thiol curing agent containing a dopamine structure, the amount of hydrochloric acid added is such that the pH of the reaction system reaches 2.5-2.6 and is maintained until the reaction is completed.
[0015] Furthermore, the preparation method of the waterproof enhancement agent comprises the following steps: adding chitosan to a 2% acetic acid solution, heating to 60-62°C and stirring to dissolve, adding dopamine hydrochloride and laccase, stirring at room temperature for 24 hours to obtain polydopamine; adding chitosan to a 2% acetic acid solution, heating to 60-62°C and stirring to dissolve, adding polydopamine and xanthan gum, stirring evenly to obtain a waterproof enhancement agent; Furthermore, in the preparation process of the polydopamine, the mass ratio of chitosan: dopamine hydrochloride: laccase is 60:0.6:2.1; in the preparation process of the waterproof enhancement agent, the mass ratio of chitosan: polydopamine: xanthan gum is 3:50:3.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. In order to solve the problem of adhesion of the current paint coating, the present invention prepares a polydopamine synthesized by the enzymatic action of laccase in the presence of chitosan, and further prepares a waterproof enhancing auxiliary agent based on the ratio of 3% chitosan, 50% polydopamine and 3% xanthan gum, and utilizes the Π-Π stacking effect between polydopamine and the dopamine structure in the thiol curing agent to achieve the purpose of improving the bonding force between the waterproof coating formed by the waterproof agent and the surface of the corrugated paper box, effectively improving the adhesion of the coating on the surface of the corrugated paper box, and the coating with strong adhesion can better resist peeling and falling off, reduce local wear and damage, and can maintain uniform distribution during friction, reduce local excessive wear or damage, and achieve the ability to improve the wear resistance of the coating.
[0017] 2. The present invention uses lignin derivatives prepared by reacting lignin with palm oil and hydroxyl-terminated polydimethylsilane as the main waterproof units and wear-resistant units, providing excellent milk performance and wear resistance for corrugated boxes. Further, eugenol is used to modify the thiol curing agent to make it contain a dopamine structure. In addition to removing the thiol olefin click chemical curing effect, it can also play the role of connecting the waterproofing agent and the waterproofing enhancing auxiliary agent. The thiol curing agent tightly connects the waterproofing agent layer and the waterproofing enhancing auxiliary agent layer, and the waterproofing enhancing auxiliary agent layer tightly connects the thiol curing agent and the waterproofing agent cross-linking curing layer and the corrugated box substrate. The layers interact with each other and are closely connected, so that the waterproof coating and the surface of the corrugated box form a firm whole, which greatly improves the hydrophobicity and wear resistance of the waterproof layer. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the following examples, the molecular weight of chitosan is 50000-190000Da, and the degree of deacetylation is 75-85%; hydroxyl-terminated polydimethylsilane Mn=2000g / moL, purity 92%; palm oil CAS: 8002-75-3; high-strength corrugated paperboard raw material Nine Dragons corrugated paperboard was purchased from Nine Dragons Paper Co., Ltd., E-flute corrugated paperboard; ultraviolet intensity is 365nm, 15W; the remaining raw materials are all commercially available.
[0020] The preparation method of lignin comprises the following steps: The empty oil palm fruit bunches are cleaned, cut into small pieces, and placed in a hot air furnace for drying for 72 hours. The dried small pieces of empty oil palm fruit bunches are placed in a rotary cooker, and 20% sodium hydroxide solution is added, and heated to 170°C for 2 hours to obtain a 1:15 w / v suspension of empty oil palm fruit bunches; the empty oil palm fruit bunch slurry is filtered to separate the black liquor, and soluble lignin in the black liquor is precipitated with 4M sulfuric acid until the pH of the liquid drops to 5. The old lignin is filtered through filter paper, washed with deionized water, vacuum dried at 70°C for 48 hours, ground, sieved with 200 mesh, and stored at room temperature away from light to obtain lignin.
[0021] The preparation method of a thiol curing agent containing a dopamine structure comprises the following steps: step (1): adding 5.15 g of eugenol and 14.8 g of triethylsilane into a reaction container, stirring evenly, adding 80 mg of tri(pentafluorophenyl)borane twice, reacting at room temperature for 12 hours, adding dichloromethane to dilute, removing impurities with basic alumina, and performing reduced pressure distillation to obtain grafted eugenol; Step (2): 3.5 g of grafted eugenol, 4.7 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, and 35.2 mg of 2,2-dimethoxy-2-phenylacetophenone were added to tetrahydrofuran, and the solution was purged with nitrogen for 5 min. The solution was irradiated with ultraviolet light for reaction for 1 h. Impurities were filtered out using a 0.2 μm syringe filter, and the solution was distilled under reduced pressure to obtain grafted pentaerythritol tris(3-mercaptopropionic acid) ester. Step (3): Add the grafted tri(3-mercaptopropionic acid) pentaerythritol ester into tetrahydrofuran, add hydrochloric acid, stir and react for 24 hours, and distill under reduced pressure to obtain a thiol curing agent containing a dopamine structure.
[0022] The preparation method of a waterproof enhancing agent comprises the following steps: adding 60 g of chitosan to a 2% acetic acid solution, heating to 60°C and stirring to dissolve, adding 0.6 g of dopamine hydrochloride and 2.1 g of laccase, stirring and reacting at room temperature for 24 hours to obtain polydopamine; adding 3 g of chitosan to a 2% acetic acid solution, heating to 60°C and stirring to dissolve, adding 50 g of polydopamine and 3 g of xanthan gum, stirring evenly to obtain a waterproof enhancing agent.
[0023] Example 1: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S1: Add 3 g of lignin to 30 mL of acetone, stir evenly, add 3 g of palm oil concentrated sulfuric acid mixture, heat to 70 ° C under nitrogen atmosphere for reaction for 2.5 h, cool to room temperature, wash the product with pentane, vacuum dry for 48 h, grind and crush, sieve to obtain a lignin derivative; S2: Add 5 mmol of lignin derivative to acetone, stir evenly, add 1 mmol of silane coupling agent KH550, stir and react at room temperature for 48 hours, add 3 mmol of dicyclohexylmethane diisocyanate, stir and react at room temperature for 24 hours, wash the product with pentane, vacuum dry for 48 hours, grind and crush, sieve, and graft the lignin derivative; S3: 15.5 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C for 4-4.5 hours under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The reaction was kept warm for 4 hours. Methanol was added, the mixture was stirred for 2 hours, and vacuum dried for 48 hours to obtain a waterproofing agent. S4: Add a thiol curing agent containing a dopamine structure into tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent into tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply a waterproofing enhancer on the surface of the corrugated box, and then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1 hour, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
[0024] The coating thickness of the waterproof enhancer is 20 μm, the coating thickness of the curing agent solution is 10 μm, and the coating thickness of the waterproofing agent solution is 30 μm.
[0025] Embodiment 2: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S3: 20.5 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C under a nitrogen atmosphere for 4-4.5 hours. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added, and the reaction was kept warm for 4 hours. Methanol was added, and the mixture was stirred for 2 hours. The mixture was dried in a vacuum for 48 hours to obtain a waterproofing agent. The remaining steps are the same as those in Example 1.
[0026] Embodiment 3: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S3: 20.5 mmol grafted lignin derivative and 10 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C for 4-4.5 hours under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The reaction was kept warm for 4 hours. Methanol was added, the mixture was stirred for 2 hours, and vacuum dried for 48 hours to obtain a waterproofing agent. The remaining steps are the same as those in Example 1.
[0027] Comparative Example 1: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S1: Add 22 g of palm oil to a reaction vessel, heat to 100 ° C and stir for 1 h under a nitrogen atmosphere, cool to 60 ° C, add 13.4 g of diethanolamine and 0.28 mL of sodium methoxide, react for 4 h, add the product to dichloromethane, rinse with saturated sodium chloride aqueous solution, dry the organic phase with magnesium sulfate, and evaporate the solvent to obtain a dihydroxy palm oil derivative; S2: 7 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and then 20 mmol dicyclohexylmethane diisocyanate and 0.05 mmol dibutyl tin dilaurate were added. The mixture was heated to 70°C for reaction for 4-4.5 h under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The mixture was kept warm for reaction for 4 h. Methanol was added, the mixture was kept warm with stirring for 2 h, and vacuum dried for 48 h to obtain a waterproofing agent. S3: Add a thiol curing agent containing a dopamine structure into tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent into tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply a waterproofing enhancer on the surface of the corrugated box, and then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1 hour, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
[0028] The coating thickness of the waterproof enhancer is 20 μm, the coating thickness of the curing agent solution is 10 μm, and the coating thickness of the waterproofing agent solution is 30 μm.
[0029] Comparative Example 2: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S1: Add 3 g of lignin to 30 mL of acetone, stir evenly, add 3 g of palm oil concentrated sulfuric acid mixture, heat to 70 ° C under nitrogen atmosphere for reaction for 2.5 h, cool to room temperature, wash the product with pentane, vacuum dry for 48 h, grind and crush, sieve to obtain a lignin derivative; S2: Add 5 mmol of lignin derivative to acetone, stir evenly, add 1 mmol of silane coupling agent KH550, stir and react at room temperature for 48 hours, add 3 mmol of dicyclohexylmethane diisocyanate, stir and react at room temperature for 24 hours, wash the product with pentane, vacuum dry for 48 hours, grind and crush, sieve, and graft the lignin derivative; S3: 15.5 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C for 4-4.5 hours under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The reaction was kept warm for 4 hours. Methanol was added, the mixture was stirred for 2 hours, and vacuum dried for 48 hours to obtain a waterproofing agent. S4: Add a thiol curing agent containing a dopamine structure into tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent into tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply the curing agent solution on the waterproofing enhancer layer, and then apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1 hour, and dry at room temperature to obtain a high-strength corrugated paper box based on the waterproofing agent.
[0030] The coating thickness of the waterproof enhancer is 20 μm, the coating thickness of the curing agent solution is 10 μm, and the coating thickness of the waterproofing agent solution is 30 μm.
[0031] Comparative Example 3: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S1: Add 3 g of lignin to 30 mL of acetone, stir evenly, add 3 g of palm oil concentrated sulfuric acid mixture, heat to 70 ° C under nitrogen atmosphere for reaction for 2.5 h, cool to room temperature, wash the product with pentane, vacuum dry for 48 h, grind and crush, sieve to obtain a lignin derivative; S2: Add 5 mmol of lignin derivative to acetone, stir evenly, add 1 mmol of silane coupling agent KH550, stir and react at room temperature for 48 hours, add 3 mmol of dicyclohexylmethane diisocyanate, stir and react at room temperature for 24 hours, wash the product with pentane, vacuum dry for 48 hours, grind and crush, sieve, and graft the lignin derivative; S3: 15.5 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C for 4-4.5 hours under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The reaction was kept warm for 4 hours. Methanol was added, the mixture was stirred for 2 hours, and vacuum dried for 48 hours to obtain a waterproofing agent. S4: Add pentaerythritol tetrakis(3-mercaptobutyrate) to tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent to tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply a waterproofing enhancer on the surface of the corrugated box, and then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1 hour, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
[0032] The coating thickness of the waterproof enhancer is 20 μm, the coating thickness of the curing agent solution is 10 μm, and the coating thickness of the waterproofing agent solution is 30 μm.
[0033] Comparative Example 4: A method for preparing a high-strength corrugated paper box based on a waterproofing agent, comprising the following preparation steps: S1: Add 3 g of lignin to 30 mL of acetone, stir evenly, add 3 g of palm oil concentrated sulfuric acid mixture, heat to 70 ° C under nitrogen atmosphere for reaction for 2.5 h, cool to room temperature, wash the product with pentane, vacuum dry for 48 h, grind and crush, sieve to obtain a lignin derivative; S2: Add 5 mmol of lignin derivative to acetone, stir evenly, add 1 mmol of silane coupling agent KH550, stir and react at room temperature for 48 hours, add 3 mmol of dicyclohexylmethane diisocyanate, stir and react at room temperature for 24 hours, wash the product with pentane, vacuum dry for 48 hours, grind and crush, sieve, and graft the lignin derivative; S3: 10.5 mmol grafted lignin derivative and 3 mmol hydroxyl-terminated polydimethylsiloxane were added to a reaction container, and 0.05 mmol dibutyl tin dilaurate was added. The reaction was heated to 70°C for 4-4.5 hours under a nitrogen atmosphere. 7 mmol 1,4-butanediol and 3 mmol N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide were added. The reaction was kept warm for 4 hours. Methanol was added, the mixture was stirred for 2 hours, and vacuum dried for 48 hours to obtain a waterproofing agent. S4: Add a thiol curing agent containing a dopamine structure into tetrahydrofuran, stir evenly to obtain a curing agent solution; add a waterproofing agent into tetrahydrofuran, stir evenly to obtain a waterproofing agent solution, apply a waterproofing enhancer on the surface of the corrugated box, and then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1 hour, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
[0034] The coating thickness of the waterproof enhancer is 20 μm, the coating thickness of the curing agent solution is 10 μm, and the coating thickness of the waterproofing agent solution is 30 μm.
[0035] Experiment: Waterproof performance test: The surface of the high-strength corrugated paper box based on the waterproofing agent prepared in the above examples and comparative examples was subjected to a static contact angle test; Sandpaper with a mesh size of 600 was placed on the surface of the water-resistant corrugated packaging material prepared in the embodiment and the comparative example, and then the sandpaper was dragged 10 times under the pressure of a 400 g weight, each dragging distance being 20 cm, and finally the static contact angle after dragging was retested.
[0036] The experimental results are shown in Table 1 below.
[0037] Table 1 Experimental data of high-strength corrugated paperboard based on waterproofing agent
[0038] Conclusion: The corrugated paper box prepared by the present invention has excellent waterproof and wear resistance.
[0039] Comparative Example 1 uses a dihydroxy palm oil derivative instead of a grafted lignin derivative, resulting in reduced waterproofing and abrasion resistance.
[0040] Comparative Example 2 did not use a waterproof enhancing agent, which resulted in reduced adhesion between the coatings and affected wear resistance.
[0041] The curing agent in Comparative Example 3 does not contain a dopamine structure and lacks a Π-Π stacking effect, which results in reduced adhesion between the coatings and affects the wear resistance.
[0042] In comparative example 4, the addition amount of the grafted lignin derivative is relatively low, resulting in a reduction in the cross-linked solidification structure and a decrease in the density of the coating. At the same time, the lignin and grafted long-chain alkane segments are reduced, resulting in a decrease in the waterproof and wear resistance.
[0043] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high-strength corrugated paper box based on a waterproofing agent, characterized in that: The method comprises the following preparation steps: S1: adding lignin to acetone, stirring evenly, adding palm oil concentrated sulfuric acid mixture, heating to 70-75°C under nitrogen atmosphere for reaction for 2.5-3h, cooling to room temperature, washing the product with pentane, vacuum drying, grinding and sieving to obtain a lignin derivative; S2: adding the lignin derivative to acetone, stirring evenly, adding the silane coupling agent KH550, stirring and reacting at room temperature for 48 hours, adding dicyclohexylmethane diisocyanate, stirring and reacting at room temperature, washing the product with pentane, vacuum drying, grinding and crushing, sieving, and grafting the lignin derivative; S3: adding the grafted lignin derivative and hydroxyl-terminated polydimethylsiloxane to a reaction container, adding dibutyl tin dilaurate, heating to 70-75°C under a nitrogen atmosphere for reaction for 4-4.5 hours, adding 1,4-butanediol and N,N-dimethylformamide solution of bis(4-hydroxyphenyl) disulfide, keeping the temperature for reaction for 4-4.5 hours, adding methanol, keeping the temperature for stirring for 2-3 hours, and vacuum drying to obtain a waterproofing agent; S4: adding a thiol curing agent containing a dopamine structure into tetrahydrofuran and stirring the mixture to obtain a curing agent solution; Add the waterproofing agent into tetrahydrofuran and stir evenly to obtain a waterproofing agent solution, apply the waterproofing enhancer on the surface of the corrugated box, then apply the curing agent solution on the waterproofing enhancer layer, and finally apply the waterproofing agent solution on the curing agent solution layer, cure with ultraviolet light for 1-2 hours, and dry at room temperature to obtain a high-strength corrugated box based on the waterproofing agent.
2. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 1, characterized in that: During the preparation of the lignin derivative, 1 g of lignin was dissolved in 10 mL of acetone, and the mass ratio of the acetone solution of lignin to the palm oil concentrated sulfuric acid mixture was 1:(1-2). In the palm oil concentrated sulfuric acid mixture, 0.1 mL of concentrated sulfuric acid was added to every 15 g of palm oil.
3. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 1, characterized in that: In the preparation process of the grafted lignin derivative, the molar ratio of silane coupling agent KH550:lignin derivative:dicyclohexylmethane diisocyanate is 1:(5-6):(2-4).
4. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 1, characterized in that: In the preparation process of the waterproofing agent, the molar ratio of the grafted lignin derivative: hydroxyl-terminated polydimethylsiloxane: 1,4-butanediol: bis(4-hydroxyphenyl) disulfide is (15.5-20.5):(3-10):7:
3.
5. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 1, characterized in that: The preparation method of the thiol curing agent containing a dopamine structure comprises the following steps: step (1): adding eugenol and triethylsilane into a reaction container, stirring evenly, adding tri(pentafluorophenyl)borane twice, reacting at room temperature, adding dichloromethane to dilute, removing impurities with basic alumina, and performing reduced pressure distillation to obtain grafted eugenol; Step (2): adding grafted eugenol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester and 2,2-dimethoxy-2-phenylacetophenone into tetrahydrofuran, purging the solution with nitrogen for 5-10 minutes, irradiating with ultraviolet light for reaction for 1-1.5 hours, filtering impurities, and distilling under reduced pressure to obtain grafted pentaerythritol tris(3-mercaptopropionic acid) ester; Step (3): adding the grafted tri(3-mercaptopropionic acid) pentaerythritol ester to tetrahydrofuran, adding hydrochloric acid, stirring for reaction, and performing vacuum distillation to obtain a thiol curing agent containing a dopamine structure.
6. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 5, characterized in that: In the preparation process of grafted eugenol, the mass ratio of eugenol to triethylsilane is (5.15-5.2):(14.8-15). The interval between the two additions of tris(pentafluorophenyl)borane is 1 hour.
7. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 5, characterized in that: In the preparation process of grafted tris(3-mercaptopropionic acid) pentaerythritol ester, the mass ratio of grafted eugenol to tetra(3-mercaptopropionic acid) pentaerythritol ester is (3.5-3.6):(4.7-4.8).
8. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 5, characterized in that: During the preparation of the thiol curing agent containing a dopamine structure, the amount of hydrochloric acid added is such that the pH of the reaction system is 2.5-2.6 and maintained until the reaction is completed.
9. The method for preparing a high-strength corrugated paper box based on a waterproofing agent according to claim 1, characterized in that: The preparation method of the waterproof enhancement agent comprises the following steps: adding chitosan to a 2% acetic acid solution, heating to 60-62°C and stirring to dissolve, adding dopamine hydrochloride and laccase, stirring at room temperature to react, and obtaining polydopamine; adding chitosan to a 2% acetic acid solution, heating to 60-62°C and stirring to dissolve, adding polydopamine and xanthan gum, and stirring evenly to obtain the waterproof enhancement agent; In the preparation process of polydopamine, the mass ratio of chitosan: dopamine hydrochloride: laccase is 60:0.6:2.1; in the preparation process of the waterproof enhancement agent, the mass ratio of chitosan: polydopamine: xanthan gum is 3:50:
3.
10. A high-strength corrugated paper box based on a waterproofing agent prepared according to the method for preparing a high-strength corrugated paper box based on a waterproofing agent according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of weather-proofing cement-base waterproof coating
CN106495603A
Star-shaped nano-glue for underwater repair and preparation method of star-shaped nano-glue
CN109161366A
Double-bonded eugenol cross-linked mussel-imitated high-adhesion hydrogel and preparation method thereof
CN111825793A
Hydrophobic, oil-resistant and degradable lignin-based waterborne polyurethane for paper coating and preparation method of hydrophobic, oil-resistant and degradable lignin-based waterborne polyurethane
CN117924641A
Adhesive materials and methods of making and using the same
US20160160097A1